2019
DOI: 10.1108/jepp-04-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial ecosystems in Poland: panacea, paper tiger or Pandora’s box?

Abstract: Purpose The purpose of this paper is to critically examine the role of public policy in the formation of entrepreneurial ecosystems in Poland. Design/methodology/approach The paper assumes a qualitative approach to researching and analysing how public policy enables and constrains the formation of entrepreneurial ecosystems. The authors conducted a series of focus groups with regional and national policy makers, enterprises and intermediaries in three Polish voivodeships (regions) – Malopolska, Mazowieckie a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Based on the demand for innovation and experiential entrepreneurial competencies (Constanţa-Nicoleta et al, 2015 ), game designers simulate a real business environment for learners to run a virtual business (Mennecke et al, 2008 , 2008 ) and avoid risks in the real world so that the cost and uncertainty of being entrepreneurs decrease. Except for general effectiveness (Tasnim, 2013 ), scholars focused on the entrepreneurial mindset, entrepreneurial intention and motivation (Buzady & Almeida, 2019 ; Ruiz-Alba et al, 2019 ), entrepreneurial behavior (Fellnhofer, 2015 ) and entrepreneurial competencies (Williams, 2015 ). Mayer et al ( 2014 ) narrowed the research subjects into engineering students, which showed gaming experience could significantly influence EE.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the demand for innovation and experiential entrepreneurial competencies (Constanţa-Nicoleta et al, 2015 ), game designers simulate a real business environment for learners to run a virtual business (Mennecke et al, 2008 , 2008 ) and avoid risks in the real world so that the cost and uncertainty of being entrepreneurs decrease. Except for general effectiveness (Tasnim, 2013 ), scholars focused on the entrepreneurial mindset, entrepreneurial intention and motivation (Buzady & Almeida, 2019 ; Ruiz-Alba et al, 2019 ), entrepreneurial behavior (Fellnhofer, 2015 ) and entrepreneurial competencies (Williams, 2015 ). Mayer et al ( 2014 ) narrowed the research subjects into engineering students, which showed gaming experience could significantly influence EE.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
“…Furthermore, Bellotti et al ( 2014 ) analyzed the entrepreneurial mindset of engineering students. In general, the relationship between SGs and entrepreneurship intention and skills is positive (Almeida, 2017 ; Bellotti et al, 2014 ; Buzady & Almeida, 2019 ; Fellnhofer, 2015 ; Ruiz-Alba et al, 2019 ), even long-term positive effectiveness (Kriz & Auchter, 2016 ). However, the study of Newbery et al ( 2016 ) found a significant negative impact for the authentic learning method, perhaps because students understood the complexity of starting a business (Protopsaltis et al, 2013 ).…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing studies on governance point out that large-scale social change comes from better cross-sector coordination rather than from the isolated intervention of individual organizations (Kania and Kramer, 2011). The ecosystem approach needs to include experimental governance from a systemic point of view – with goals, metrics, and decision making that involve a widening circle of actors (Brooks et al., 2019). Balancing policy measures for both short-term growth (i.e.…”
Section: Policy Diversitymentioning
confidence: 99%